Effects of temperature and salinity during the embryonic period of Chirostoma humboldtianum and Chirostoma riojai (Atherinopsidae) until hatching - Hernández-Rubio, M. C.; Figueroa-Lucero, G. (HIDROBIOLÓGICA, 2017)
-